Local Political Budget Cycles in a Federation: Evidence from West German Cities - Marina Furdas; Katerina Homolkova; Krisztina Kis-Katos (Institute for the Study of Labor (IZA), 2015)
This paper analyzes the occurrence of political budget cycles in 604 West German cities between 1975 and 2007. Due to the idiosyncratic timing of state and local elections, the budgetary changes before elections at two tiers of the federalist government can be separately estimated and can also be distinguished from common time effects. Both local and state elections result in pre-election manipulation of the local finances of moderate size. Before both types of elections, we observe an increase in building investments, accompanied by increasing intergovernmental grants for investment purposes but also a halt in the increase of local tax rates. By contrast, elections at the two tiers of the government affect the size of the current budget differently: current revenues and expenditures decrease before local but increase before state elections, suggesting a difference in the tightness of the local budget constraint. The extent of these political budget cycles is more pronounced in municipalities that are politically aligned with the state governments and are politically more contested.
Keywords: D72; H71; H72; 330; political budget cycles; German cities; municipal finances; local and state elections